Monitoring the re-growth rate of alien vegetation after fire on Agulhas Plain, South Africa - Fatoki, Oluwakemi Busayo (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Geography and Environmental Studies))--University of Stellenbosch, 2007.